Feasibility of Grocery Cooperatives for Improving Food Access in High- Deprivation Urban Communities: A Case Study of the Altgeld Gardens Neighborhood; Chicago, IL - Moths, Jessica (My University, 2012)
Final report from a case study on the feasibility of a grocery cooperative in the Altgeld Gardens neighborhood in Chicago, IL. This paper covers the community stakeholders, financial considerations, and land availability.
Keywords: food access; Chicago; food deserts; community food security; urban planning; Altgeld Gardens; grocery cooperatives